2021
DOI: 10.3233/sw-210434
|View full text |Cite
|
Sign up to set email alerts
|

Towards fully-fledged archiving for RDF datasets

Abstract: The dynamicity of RDF data has motivated the development of solutions for archiving, i.e., the task of storing and querying previous versions of an RDF dataset. Querying the history of a dataset finds applications in data maintenance and analytics. Notwithstanding the value of RDF archiving, the state of the art in this field is under-developed: (i) most existing systems are neither scalable nor easy to use, (ii) there is no standard way to query RDF archives, and (iii) solutions do not exploit the evolution p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…There are several ways to implement this idea in RDF, such as RDF reification [18], singleton properties [25], and named graphs [7]. However, these mechanisms have significant shortcomings [11,16,19,26].…”
Section: Preliminariesmentioning
confidence: 99%
“…There are several ways to implement this idea in RDF, such as RDF reification [18], singleton properties [25], and named graphs [7]. However, these mechanisms have significant shortcomings [11,16,19,26].…”
Section: Preliminariesmentioning
confidence: 99%
“…As such, this hybrid storage approach is a step towards solving the need for properly preserving RDF on the Web. A recent survey [21] has shown that existing RDF archiving solutions fail to handle large RDF archives with many versions. It was shown that the hybrid approach employed by OSTRICH is the only one capable of storing large RDF archives, but that it suffers from a scalability issue in terms of ingestion time for many versions.…”
Section: Taelman Et Al / Optimizing Storage Of Rdf Archives Using Bid...mentioning
confidence: 99%
“…Since the complex graph data archives ensure permanent, diversified, highly scaleable, and efficient analytical and VOLUME 11, 2023 query processing capabilities for future application demands for many emerging databases and graph processing frameworks [8]- [10], RDF (Resource Description Framework) graph data archives must be a use-case for DNA storage. DNA-based RDF graph data archives should, therefore, be able to retrieve partial information using an effective queryprocessing mechanism when analyzing advanced data analytics.…”
mentioning
confidence: 99%